Principles of Emergence of Urban Literature of the 17th Century in Japanese Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The urban culture of the 17th century has come a long way. A large part of all works of art began to be intended for a new audience - city dwellers. The works were dedicated to the image of their life, interests, worries, and desires. The life of the city, the people who live in it have become the subject of art. This article talks about the factors that caused the creation of urban literature.